The Effect of Emotional Intelligence on Emotion Regulation among Juvenile Offenders at LPKA Class I Kutoarjo - Aditya Saputra; Ali Muhammad; Umar Anwar; Budi Priyatmono (Psikoislamedia: Jurnal Psikologi, 2026)
In early 2025, 28 inmates at the Kutoarjo Class I Correctional Facility committed violations, representing the highest rate recorded in the past five years. This study aimed to examine the influence of emotional intelligence on emotion regulation among inmates. Employing a quantitative correlational design, the study involved 92 participants. Data were collected using the Wong and Law Emotional Intelligence Scale and the Emotion Regulation Questionnaire. The findings indicated that emotional intelligence has a significant effect on emotion regulation (p < 0.05; R² = 0.280). This suggests that emotional intelligence accounts for 28% of the variance in emotion regulation, while the remaining 72% is influenced by other unexamined factors. These results underscore the important role of emotional intelligence in shaping adaptive emotional regulation and highlight the need for targeted rehabilitation programs to enhance inmates’ psychological competencies and support successful social reintegration.